Multidimensional gas chromatographic techniques applied to the analysis of lipids from wild‐caught and farmed marine species. Issue 2 (8th May 2016) - Costa, Rosaria; Albergamo, Ambrogina; Piparo, Marco; Zaccone, Giacomo; Capillo, Gioele; Manganaro, Antonio; Dugo, Paola; Mondello, Luigi
Abstract : Comprehensive two‐dimensional gas chromatography‐mass spectrometry was exploited for the obtainment of fatty acid fingerprints in fish and molluscs from South Italy. Scope of the lipidomic investigation was to highlight differences in the fatty acid profiles of samples from aquaculture and from the wild. The fish species under investigation were Sparus aurata and Dicentrarchus labrax, typically cultivated in Italy and commonly found in the fish market. Another aim was to find a correlation between the diet fed to fish and the expression of specific fatty acids in muscle composition. Beyond fish, two species of bivalves were analyzed to assess their lipidomic composition: Mytilus galloprovincialis (mussels) and Venerupis aurea var. laeta (clams). Both species originated from two salt lakes in South Italy. GC × GC–MS analysis showed that omega‐3 fatty acids were naturally more concentrated in wild fish, whereas their presence in cultivated fish was lower and in favor of omega‐6 and oleic acids, as an evident consequence of food supplementation. Bivalves reported a consistent amount of PUFA, although presenting some differences in the quality of fatty acids. As an additional parameter of investigation, the content of mercury was determined in all the samples by means of a Direct Mercury Analyzer, based on Atomic Absorption Spectroscopy. Wild fish reported a level of mercury that was ten times higher than in aquafarmed fish, and the maximum amount tolerated by the EC regulation. On the contrary, the level of mercury in molluscs was in general very low, particularly when compared with samples from other Italian sites of collection. Practical applications: One of the possible applications of the GC × GC methodology here presented could be the detection of a common food fraud. In the Mediterranean Sea, gilthead sea bream and sea bass are today rarely found in sea open waters. Basically, fish sold in the market comes from cultivation. Due to the fact that wild fish is more appreciated by the consumer, quite often fish sellers are encouraged to lie about the real origin of fish. The bidimensional plots shown in this study represent an extraordinary tool for differentiating the two types of fish. Also, this study provides substantial support to aquafarmers, who can draw useful advice on how to tune optimal diets to be fed to fish. In fact, it was demonstrated that fish feed highly affects fatty acid composition. The fatty acid composition of aquafarmed and wild caught fish and shellfish from the Mediterranean Sea was investigated. Comprehensive gas chromatography (GC × GC) was the analytical technique that allowed obtaining highly structured fingerprints of fatty acids. Abstract : The fatty acid composition of aquafarmed and wild caught fish and shellfish from the Mediterranean Sea was investigated. Comprehensive gas chromatography (GC × GC) was the analytical technique that allowed obtaining highly structured fingerprints of fatty acids.